KONSTRUKSI PENDIDIKAN NILAI DAN MORAL BAGI ANAK JALANAN DALAM MENGEMBANGKAN SMART AND GOOD CITIZEN - Wildan Nurul Fajar; Ratna Kartika Wati (Sainteks, 2012)
This study concerned on the condition of the dynamics growing problems of beggar in Banyumas, mainly related to the behavior of those who tend to be far from the values and morals. Until now the government has not been able to carry out the development of beggar is based on values and moral development. The methodology of this study is qualitavie research which used grounded theory. The data collections are documents, interview and observation. The results showed that the Guidance has not touched ethics and behavior issues that become a part of the problems of beggar. Citizenship education has a role as an educational and moral basic can be a solution for beggar become good and smart citizens. Based on these conclusions canbe recommended to the government and otherrelevant parties, is expected to make a charge of Citizenship Education in the implementation guidance and moral values to beggar will contribute to the development of good and smart citizen. Keywords: Civic Education, Education and Moral Values, Beggar, Good and SmartCitizen.